Analisis Pertumbuhan Mikroorganisme Selama Fermentasi Tapai Singkong Menggunakan Variasi Lama Inkubasi - Felisha Putri Maida; Ardi Mustakim (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2025)
Cassava tapai is a traditional Indonesian food product produced through the fermentation of cassava (Manihot esculenta) with the help of microorganisms, particularly the yeast Saccharomyces cerevisiae. This product not only has cultural and economic value but also contains bioactive compounds with health benefits, such as probiotics and fermentation metabolites. However, the quality of cassava tapai is significantly influenced by process factors, particularly incubation time. This study aimed to analyze microbial growth and changes in the chemical properties of cassava tapai with varying fermentation times. The study was conducted using an experimental design with fermentation times of 24, 48, and 72 hours at room temperature. The main parameters observed included the number of microbial colonies (cfu/g), pH changes, and alcohol content produced during the fermentation process. The results showed that microbial growth increased significantly, peaking at 48 hours, with the highest colony count compared to other treatments. After 72 hours, the number of colonies decreased, likely due to ethanol accumulation and decreased substrate availability, which reduced microbial activity. The pH value tended to decrease with increasing fermentation time, reflecting the formation of organic acids during the process. Meanwhile, the alcohol content showed an increasing trend from the beginning to the end of fermentation, although the growth rate was relatively slower at 72 hours. These findings confirm that varying incubation length significantly influences microbial dynamics and chemical changes in cassava tapai. The optimal fermentation time is around 48 hours, as this is the phase where the balance between microbial growth, alcohol formation, and sensory characteristics is maintained. The results of this study can serve as a basis for developing standards for cassava tapai production at both household and industrial scales, while also strengthening efforts to preserve traditional foods with a modern scientific approach.